Sin City? - Pieter A. Gautier; Michael Svarer; Coen N. Teulings (Tinbergen Institute, 2007)
Is moving to the countryside a credible commitment device for couples? Weinvestigate whether lowering the arrival rate of potential alternative partners bymoving to a less populated area lowers the dissolution risk for a sample of Danishcouples. We find that of the couples who married in the city, the ones who stay inthe city have significant higher divorce rates. Similarly, for the couples who marriedoutside the city, the ones who move to the city are more likely to divorce. Thiscorrelation can be explained by both a causal and a sorting effect. We disentanglethem by using the timing-of-events approach. In addition we use information on father'slocation as an instrument. We find that the sorting effect dominates. Movingto the countryside is therefore not a cheap way to prolong relationships.
Keywords: J12; J64; 330; Dissolution; search; mobility; city; Wohnstandort; Stadt; Ländlicher Raum; Binnenwanderung; Soziale Beziehungen; Ehe; Dänemark